Genome-Wide Investigation of the Phospholipase C Gene Family in Zea mays - Zhu, Jiantang; Zhou, Yuanyuan; Li, Jiale; Li, Hui (Frontiers in Genetics, 2021)
Phospholipase C (PLC) is one of the main hydrolytic enzymes in the metabolism of phosphoinositide and plays an important role in a variety of signal transduction processes responding to plant growth, development, and stress. Although the characteristics of many plant PLCs have been studied, PLC genes of maize have not been comprehensively identified. According to the study, five phosphatidylinositol-specific PLC (PI-PLC) and six non-specific PLC (NPC) genes were identified in maize. The PI-PLC and NPC genes of maize are conserved compared with homologous genes in other plants, especially in evolutionary relationship, protein sequences, conserved motifs, and gene structures. Transient expression of ZmPLC-GFP fusion protein in Arabidopsis protoplast cells showed that ZmPLCs are multi-localization. Analyses of transcription levels showed that ZmPLCs were significantly different under various different tissues and abiotic stresses. Association analysis shown that some ZmPLCs significantly associated with agronomic traits in 508 maize inbred lines. These results contribute to study the function of ZmPLCs and to provide good candidate targets for the yield and quality of superior maize cultivars.